Cholelithiasis in Down's syndrome. Issue 3 (1st September 2001) - Toscano, E; Trivellini, V; Andria, G
Abstract : Cholelithiasis is considered uncommon in infancy, childhood, and adolescence. We performed a prospective, controlled study showing that children with Down's syndrome have a significantly higher prevalence of cholelithiasis (4.7%) compared with controls (0.2%). Clinicians should be aware of the risk of gallstones in children with Down's syndrome.